Identification of genomic alterations in nasopharyngeal carcinoma and nasopharyngeal carcinoma-derived Epstein–Barr virus by whole-genome sequencing. (9th August 2018) - Tu, Chaofeng; Zeng, Zhaoyang; Qi, Peng; Li, Xiayu; Guo, Can; Xiong, Fang; Xiang, Bo; Zhou, Ming; Liao, Qianjin; Yu, Jianjun; Li, Yong; Li, Xiaoling; et al.
Abstract: Nasopharyngeal carcinoma (NPC) is a common tumor in southern China with marked ethnic and geographic distributions and concomitant Epstein–Barr virus (EBV) infection. However, the molecular basis of NPC remains largely unknown, and the role of EBV genomic variations in the pathogenesis of NPC is unclear. Whole-genome sequencing of a collection of 12 EBV-positive paired NPC tumor/peripheral blood samples from Hunan Province was performed, and the FBXO11 gene was subjected to further functional analyses. We identified 69 missense mutations in signaling pathways typically altered in cancer, including NF-κB and Wnt/Hedgehog/Notch. Additionally, 122 variations were identified in non-coding regions. Among these, a subset of genes was confirmed as dysregulated in NPC by mining the NPC cDNA microarray database. The randomly selected gene, FBXO11, could promote the malignant progression of NPC in vitro . Full-length EBV genomes from 8 of the 12 patients with NPC were also successfully assembled, and latent EBV infection is a primary cause of NPC. The various subtypes of EBV detected exhibited clear correlations with its geographical distribution. This study has explored novel biological markers and tumorigenic pathways with substantial potential to enhance therapeutic strategies for NPC. Abstract : We report the first genome-wide sequencing of EBV-positive NPC samples from Hunan Province and successfully determine the mutation landscapes in both NPC and NPC-derived EBV genomes, which may contribute to improved understanding of the molecular mechanisms underlying NPC.